Film Wandy Jakubowskiej i Igora Newerlego „Król Maciuś I" (1957) – recepcja medialna i przesłanie ideowo-wychowawcze - Uljasz, Adrian (Chowanna, 2022)
In his article, Adrian Uljasz discusses media reception and the ideological and educational message of the adaptation of Janusz Korczak’s novel King Matt the First, the film King Matthew I (directed by Wanda Jakubowska, screenplay by Wanda Jakubowska and Igor Newerly) (1957). Uljasz addresses the means of artistic expression on which the authors based the educational message of this film. By media reception Uljasz understands the reception of Jakubowska and Newerly’s works in the media, from traditional printed works to the contemporary metamedium, the Internet. This research topic has gained in importance due to the anniversaries related to Korczak and Newerly. In 2022, eighty years had passed since the deaths of Korczak and his pupils and employees from the Jewish orphanage in Warsaw (1942). 1987 saw the death of Igor Newerly, educator and writer, co-author of the script for Jakubowska’s adaptation and Korczak’s close associate from the Warsaw orphanage. The film can be regarded in terms of transference of the views of these two writers-educators.